2010
DOI: 10.1159/000308303
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of <i>KLF13</i> and <i>FGFR3</i> in Oral Cancer Cells

Abstract: KLF13 and FGFR3 have important cellular functions and each is believed to play a role in cancer. KLF13 is a transcription factor required for the expression of several oncogenes. FGFR3 is a fibroblast growth factor receptor that initiates a signaling cascade leading to the activation of numerous cellular pathways. Here we show that KLF13 and FGFR3 are overexpressed in oral cancer cells. We also show that artificially reducing cellular levels of KLF13 and FGFR3 decreases cell proliferation and increases sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 68 publications
1
47
0
Order By: Relevance
“…Translocation events implicating the FGFR1 gene and various fusions of FGFR1 are found in myeloproliferative syndromes (12); chromosomal translocations of FGFR1 or FGFR3 and the transforming acidic coiled-coil genes (TACC1 or TACC3) are oncogenic in glioblastoma multiforme, bladder cancer, head and neck cancer, and lung cancer (13)(14)(15)(16); oncogenic mutations of FGFR2 and FGFR3 are observed in lung squamous cell carcinoma; FGFR2 N549K is observed in 25% of endometrial cancers; FGFR3 t(4;14) alterations are reported in 15-20% of multiple myeloma (17)(18)(19); FGFR4 Y367C mutation in the transmembrane domain drives constitutive activation and enhanced tumorigenic phenotypes in a breast carcinoma cell line (20)(21)(22); and K535 and E550 mutants are reported to activate FGFR4 in rhabdomyosarcoma (23). FGFR amplification is reported in various cancers (24,25): FGFR1 is amplified in colorectal, lung, and renal cell cancers (26,27); FGFR2 is amplified in gastric cancer and colorectal cancer (28,29); FGFR3 is commonly amplified in bladder cancer and also is reported for cervical, oral, and hematological cancers (30)(31)(32); and FGFR4 is amplified in hepatocellular carcinoma, gastric cancer, pancreatic cancer, and ovarian cancer (33)(34)(35)(36)(37). FGFR also is involved in autocrine activation of STAT3 as a positive feedback in many drug-treated cancer cells which are driven by diverse oncogenes such as EGFR, ALK, MET, and KRAS (38).…”
Section: Significancementioning
confidence: 99%
“…Translocation events implicating the FGFR1 gene and various fusions of FGFR1 are found in myeloproliferative syndromes (12); chromosomal translocations of FGFR1 or FGFR3 and the transforming acidic coiled-coil genes (TACC1 or TACC3) are oncogenic in glioblastoma multiforme, bladder cancer, head and neck cancer, and lung cancer (13)(14)(15)(16); oncogenic mutations of FGFR2 and FGFR3 are observed in lung squamous cell carcinoma; FGFR2 N549K is observed in 25% of endometrial cancers; FGFR3 t(4;14) alterations are reported in 15-20% of multiple myeloma (17)(18)(19); FGFR4 Y367C mutation in the transmembrane domain drives constitutive activation and enhanced tumorigenic phenotypes in a breast carcinoma cell line (20)(21)(22); and K535 and E550 mutants are reported to activate FGFR4 in rhabdomyosarcoma (23). FGFR amplification is reported in various cancers (24,25): FGFR1 is amplified in colorectal, lung, and renal cell cancers (26,27); FGFR2 is amplified in gastric cancer and colorectal cancer (28,29); FGFR3 is commonly amplified in bladder cancer and also is reported for cervical, oral, and hematological cancers (30)(31)(32); and FGFR4 is amplified in hepatocellular carcinoma, gastric cancer, pancreatic cancer, and ovarian cancer (33)(34)(35)(36)(37). FGFR also is involved in autocrine activation of STAT3 as a positive feedback in many drug-treated cancer cells which are driven by diverse oncogenes such as EGFR, ALK, MET, and KRAS (38).…”
Section: Significancementioning
confidence: 99%
“…KLF13 is required for the expression of several oncogenes including cyclin D1, which is a known oncogene in oral squamous cell carcinoma (47,49). Furthermore, KLF13 is believed to play a role in cancer, and altered expression of it contributes to tumorigenesis (5053).…”
Section: Discussionmentioning
confidence: 99%
“…Our study, as well as previous publications, found variable expression of various RTKs in HNSCC cells and fibroblasts. 38,1619 Consequently, we choose a treatment agent which targeted multiple RTKs (dovitinib).…”
Section: Discussionmentioning
confidence: 99%
“…36 These receptors bind FGF-2 (FGF-basic), which has been found to be elevated in HNSCC specimens. 6 Furthermore, FGF-2 and FGFR-1 expression in tumor associated fibroblast of HNSCC specimens correlate with higher grade, increased incidence of lymph node metastasis and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%